In-flight simulation of tilt-rotor VTOL UAV using open loop wind tunnel - Wong, Amos Timothy Jun Han (Nanyang Technological University, 2022)
This project covers the design of a TRUAV, its integration with the windshaper open loop wind tunnel and the characterisation of the UAV’s dynamics. Following that, these readings would be used to help develop a controller using the tilt corridor method that would be used to control the UAV during the transition phase of flight.